Android-Based Meatball Sales System Using the Fast Method (Case Study: Bakso Rikit Kute, Rikit Bur, Southeast Aceh) - Muhammad Fani Skd; Difa Tazkia; Mailisa; Lidia Fitri Ayu (Jurnal Armada Informatika, 2026)
Micro-scale culinary businesses require fast sales recording, yet transactions, kitchen queues, ingredient usage, and cash reports are often managed in separate media. This study develops an Android-based meatball sales system design for Bakso Rikit Kute, Rikit Bur, Southeast Aceh, using the Framework for the Application of Systems Thinking (FAST). An artifact-oriented design approach covers eight stages: scope definition, problem analysis, requirements analysis, logical design, decision analysis, physical design, construction and testing, and installation planning. The result comprises six service domains, twenty core requirements, four roles, three release increments, twenty-six functional scenarios, twelve business rules, ten operational and security risk scenarios, and three recovery scenarios. The design applies an offline-first architecture, recipe-based ingredient deduction, shift reconciliation, idempotency keys, and audit trails. Traceability inspection shows that every core requirement is linked to a business problem, module, rule, and acceptance scenario. The study contributes a FAST implementation pattern that preserves decision links from business problems to Android design and test evidence. These results indicate design completeness rather than operational effectiveness because production deployment and field-impact measurement remain outside the research boundary